Sensitivity and Resolution Study of a Small-Field γ-Camera System on a Tomographic Level - Rapsomanikis, A.-N.; Zioga, M.; Mikeli, M.; Thanassas, D.; Stiliaris, E. (HNPS Advances in Nuclear Physics, 2020)
The sensitivity and the spatial resolution of a small-field γ-Camera system based on a Position Sensitive Photomultiplier Tube (PSPMT) on a tomographic level are examined in this study. A cylindrical Gel-Phantom (d = 40 mm, h = 50 mm) with cylindro-conoidal tubes and capillaries (from 64 to 640 mm3 in volume) containing water solution of 99mTc is used as a test phantom in the present work. A total of 24 projections covering the full angle region (0°-360°) are obtained with the γ-Camera system under examination. The planar information is further analyzed to reconstruct the tomographic images taking into account all off-line corrections needed to remove barreloid deformations appearing at the edges of the Field-of- View. The reconstruction procedure is performed with iterative algorithms and for comparison reasons two different techniques (MLEM and accelerated ART) are used. The variety of the 99mTc-volumes in the phantom with the given specific radioactivity and the phantom axial asymmetry, due to the diÆerent radial distances of the tubes in the gel environment, allow a realistic characterization of the system’s performance on a tomographic level. Obtained experimental results for the system sensitivity and spatial resolution are presented and discussed in this work.